Assinaturas icnológicas em depósitos glacigênicos do Grupo Itararé no RS - Lermen, Raquel Elisa (Universidade do Vale do Rio dos Sinos, 2006)
The ichnotaxonomic review of the trace fossils from Itararé Group (Paraná Basin, south of Brazil) in the Rio Grande do Sul State (southernmost Brazil) showed the presence of an ichnofauna dominated by arthropod trackways. Resting traces and intrastratal trails also made by arthropods and shallow burrows produced by soft-bodied organisms are subordinated, as well as a Chondrites-Planolites-Palaeophycus composite ichnofabic. Two new ichnospecies were diagnosed, Cruziana intermittens n. isp. e Tonganoxichnus itararensis n. isp. Two ichnocoenoses were differenciated: (i) Paleoichnocoenosis A, bearing arthropod trackways, resting traces, intrastratal trails and shallow burrows, related to the rhythmite facies; and (ii) Paleoichnocoenosis B, joining exclusively deeper burrows, related to the heterolithic deposit facies. Four distinct suites were observed in Paleoichnocoenosis A: (i) MP suite, having Maculichna varia, Protichnites isp., Diplichnites gouldi and Diplopodichnus biformis, with Kouphichnium isp. subordinated, and related to the rhythmites type A; (ii) HT suite, composed of Helmithoidichnites tenuis and Treptichnus pollardi, with Nereites isp. and Tonganoxichnus itararensis n. isp. subordinated, related to the rhythmites type B; (iii) CR suite, bearing Cruziana problematica, C. intermittens n. isp., Rusophycus carbonarius and Gluckstadtella cooperi, with H. tenuis subordinated, related to the rhythmites type C; and (iv) Dg suite, monospecific to Diplichnites gouldi, superimposed to the CR suite, in palimpsest preservation. The Paleoichnocoenosis B is formed by a composite ichnofabric of Chondrites and Planolites (deeper tier), and Palaeophycus (shallow tier). The recorded ichnological signatures suggest an estuarine, fjord-like depositional setting, the proximal zone extending to ENE (Cachoeira do Sul region) and the distal zone reaching the SSW (south of São Gabriel-southwest of Lavras do Sul). The rhythmites type B are concentrated in the proximal zone, the rhythmites type A and C, in the marginal plains, lateral to the main body water, and the heterolithic deposits characterize the estuary mouth, opening to the sea, under brackish water conditions. The ichnological and faciological characteristics of the paleoichnocoenoses A and B reveal the existence of an atypical Scoyenia Ichnofaceis and an impoverished Cruziana Ichnofacies, respectively, in the studied deposits. According to the global record, the presence of G. cooperi, M. varia, T. pollardi and T. itararensis n. isp. in the rhythmites allows to infer an Upper Carboniferous (Pennsylvanian) age to these rocks.
Keywords: Geologia; Traços fósseis; Grupo Itararé; Geology; Traces fossil; Itararé group; ACCNPQ::Ciências Exatas e da Terra::Geologia